Prefabricated and Prestressed Bio-Concrete Piles: Case Study in North Jakarta - Mohammed Mustafa Hussein AL-Amrani; Muhammed Ikhsan Setiawan; Adi Prawito (NAROTAMA UNIVERSITY, Indonesia, 2022)
In this research, we will talk about Prefabricated and Prestressed Concrete piles in general and their types, what they are manufactured and developed over the years and how much they cost according to international standards and their usefulness in overcoming soil problems and pre-construction problems, then we will talk specifically about Prefabricated and Prestressed Bio-Concrete piles and the difference between them and ordinary piles. The research will also present the opinions of people who have delved into and discussed this topic and the opinions of all engineers, economists and specialists in general. In the end, this research will conclude with a complete and simplified summary of Prefabricated and Prestressed Bio- Concrete piles and all the information related to them in foundation engineering and other points that the engineer or specialist has not encountered before.